Systems and Relations All the Way Down, All the Way Across - Tim Gough (Footprint)
This article proposes a hyper-relational theory of the world, conjoining cybernetics, information theory, general systems theory, the philosophy of Deleuze and Guattari and quantum physics in order to show that systems and relations go all the way down, all the way across.  I give an exposition of Shannon’s information theory, and draw connections with quantum mechanics. The work of Bertalanffy is discussed and its relationship to philosophy and quantum mechanics outlined.  I then critique the naïve, realist account of reality; what is proposed in its place is a hyper-relational ontology whereby entities (being) are epiphenomena of relations (becoming). The implications of this ontology in relation to architecture are discussed by contrasting it with, on the one hand, a hylomorphic approach to the essence of architecture (which foregrounds entities) and, on the other, a hermeneutic approach (which foregrounds meaning).  Buildings are epiphenomena of broader political, interpersonal, ecological and essentially relational matters, assemblages, systems and interplays, and this hyper-relationality is the ontology of architecture.